Islamic Banking and Financial System in Kazakhstan - KULIBAYEVA, Diana V.; KAZBEKOVA, Zhanat B. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
It has been established by now that the Islamic Banking and Financial system is very different from the conventional banking system. When the conventional banking is based on philosophy of capitalism, the Islamic Banking is based on principle of equity, fairness and social justice. In the process of reviewing the evolution, this has been very clear that the Islamic Banking has gained significant momentum across globe and especially in Central Asia Region from late 1990s. The similar effect is also observed in development of Islamic Banking in Kazakhstan during this period. While progress has been good and awareness also built up especially on the backdrop of global financial crisis in 2008, the growth of Islamic Banking can be accelerated. Therefore this study will attempt to look into the prospect of Islamic Banking in Kazakhstan from two different points of view. In the first place, it will look into the aspect of benefit and advantage it brings into economy, society and on the overall national interest. On the other hand, it will look into the area where corrective actions required or progressed needed to be accelerated. The whole study will be done in the form of two different models similarly to what has been experienced in the Muslim world. As part of this process, the study will also look into as to what needs to be done differently from and what are missing elements for full potential growth. At the end, the study will come out with its recommendations in all objective areas.
Keywords: Islamic banking, banking industry, financial system, banking models, banking development